Combined substrate micropatterning and FFT analysis reveals myotube size control and alignment by contact guidance. Issue 3 (22nd May 2019) - Vajanthri, Kiran Yellappa; Sidu, Rakesh Kumar; Poddar, Suruchi; Singh, Ashish Kumar; Mahto, Sanjeev Kumar
Abstract: Most important evaluating criteria for in vitro skeletal muscle models include the extent of differentiation and the degree of alignment in the tissue model. Substrate micropatterning is considered as an effective tool as it recreates in vivo like cellular microenvironment and helps in understanding the fundamental concepts and mechanisms underlying myogenesis. However, the influence of micropatterning based contact guidance cues over satellite cell alignment and myotube formation needs to be explored and studied further. In the present work, we demonstrate the regulation of myotube size control and alignment through the substrate micropatterning. For this purpose, primary myoblast cells (i.e., satellite cells) isolated from rat hind limb muscle were characterized and cultured for a period of 14 days on micropatterned glass substrates processed by the microchannnel flowed plasma process. Several characteristic parameters of muscle differentiation, including the fusion index, maturation index, and average width of the myotubes were quantified. The functional behavior of cultured myotubes exhibiting spontaneous contractions was assessed through kymograph to determine the twitch frequency. In addition, we evaluated the degree of alignment of myotubes on micropatterned substrates through examining orientation order parameter and two‐dimensional fast Fourier transform analysis. Altogether, the outcomes reveal that the contact guidance cues arising due to micropatterning of the substrates could be a key regulator for controlling the size and degree of alignment of myotubes during the myogenesis process.